Systematic review of observational studies of the impact of cardiovascular risk factors on preeclampsia in sub-saharan Africa - Oleg Iris Hounkpatin; Salimanou Ariyoh Amidou; Yessito Corine Houehanou; Philippe Lacroix; Pierre Marie Preux; Dismand Stephan Houinato; Holy Bezanahary (BMC, 2021)
Abstract Background Maternal mortality is a public health issue, particularly in low- and middle-income countries (LMIC). Sub-Saharan Africa (SSA) is the region most affected worldwide by maternal mortality, and preeclampsia is one of the main causes. We performed a systematic review of observational studies to identify the impact of cardiovascular risk factors on preeclampsia in SSA with a more representative sample. Methods Databases: PubMed and Google Scholar were searched to identify published studies. Studies were included if they reported results on the link between at least one cardiovascular risk factor and preeclampsia. Relevant studies quality was assessed with the Newcastle-Ottawa Scale (NOS). Odds ratios and relative risk (RR) were reported with their confidence intervals. Results Twelve articles (8 case-controls, 3 cohorts, 1 cross-sectional) were included in this review, with a total of 24,369 pregnant women. Cardiovascular risk factors such as chronic hypertension, overweight, obesity, diabetes and alcohol were significantly associated with a high risk of preeclampsia. Very few data were available concerning some risk factors. None of the articles reported tobacco consumption as a preeclampsia risk factor. There is a lack of data from French-speaking SSA countries. Conclusion Cardiovascular risk factors increase the risk of preeclampsia. Our results suggest the need for prospective cohort studies to ascertain this association in order to reduce maternal mortality due to preeclampsia.